2012
DOI: 10.1016/j.exer.2012.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Anti-EMP2 diabody blocks epithelial membrane protein 2 (EMP2) and FAK mediated collagen gel contraction in ARPE-19 cells

Abstract: Epithelial membrane protein 2 (EMP2) regulates collagen gel contraction by the retinal pigment epithelium cell line ARPE-19 by modulating FAK activation. Collagen gel contraction is one in vitro model for an aberrant wound healing response, proliferative vitreoretinopathy (PVR), which occurs as a complication of severe ocular trauma. The purpose of this study is to investigate whether EMP2 specific recombinant diabody decreases activation of FAK and collagen gel contraction in ARPE-19. Anti-EMP2 diabody was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…42 Expression of EMP2 was shown to drive the cellular response toward a FAK-dependent pathway. 43 In addition, activation of the Src and FAK family members and downstream signaling proteins are associated with a good prognosis in UC of the bladder. 44 As a result, we speculate that reciprocal regulation of EMP2 and caveolin-1 levels in cancer cells may reshape the cellular surface-receptor repertoire and its attendant responsiveness to the local environment.…”
Section: Discussionmentioning
confidence: 99%
“…42 Expression of EMP2 was shown to drive the cellular response toward a FAK-dependent pathway. 43 In addition, activation of the Src and FAK family members and downstream signaling proteins are associated with a good prognosis in UC of the bladder. 44 As a result, we speculate that reciprocal regulation of EMP2 and caveolin-1 levels in cancer cells may reshape the cellular surface-receptor repertoire and its attendant responsiveness to the local environment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it may be possible to use antagonists to endogenous integrin mediators or reagents designed to inhibit integrin activity to prevent or treat PVR. Recent preclinical studies have shown that decreasing the expression of epithelial membrane protein 2, a RPE cell integrin, or inhibition of it by directed antibodies reduces the onset of PVR formation (Morales et al, 2012;Telander et al, 2011). The applicability of these in vitro results to human disease is not yet known.…”
Section: A Look Into the Futurementioning
confidence: 95%
“…A number of previous studies have stated that members of the EMP family affect the integrin heterodimer repertoire on the plasma membrane, and modulation of the expression or localization of EMP proteins may alter the surface repertoire of molecules ( 54 56 ). The surface molecular repertoire, including major histocompatibility complex 1 proteins, integrins and other immunoglobulin superfamily members such as CD54 and glycosylphosphatidyl-inositol-linked proteins may be altered as the expression of EMP2 changes ( 57 ).…”
Section: Discussionmentioning
confidence: 99%